2004
DOI: 10.1177/0047287503258837
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Risk-Taking, Sensation-Seeking, and the Tourist Behavior of Young Adults: A Cross-Cultural Study

Abstract: This study analyzed the effects of the combined psychological characteristics of risk-taking and sensation seeking on the travel behavior and preferred tourist activities of young adults on leisure trips. The results of this cross-cultural study, which was conducted among 1,429 students at 11 universities located in 11 different countries, found that respondents with high combined risk-taking and sensation seeking (RSS) scores differed significantly in their travel behavior, mode of destination choice, preferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
224
2
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(250 citation statements)
references
References 46 publications
(57 reference statements)
16
224
2
8
Order By: Relevance
“…The need for novelty was found to be related to the individual lifestyle (Bello & Etzel, 1985) as well as personality (Plog, 1974). One of the most cited works associated with tourists' risk perception would be the classical work of Plog (Korstanje, 2009;Kozak et al, 2007;Lepp & Gibson, 2003;Pizam et al, 2004;Reisinger & Mavondo, 2005;Sönmez & Graefe, 1998b). Plog (1974; categorized tourists based on their personality and motivation into three scales.…”
Section: The Antecedents Of Risk Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for novelty was found to be related to the individual lifestyle (Bello & Etzel, 1985) as well as personality (Plog, 1974). One of the most cited works associated with tourists' risk perception would be the classical work of Plog (Korstanje, 2009;Kozak et al, 2007;Lepp & Gibson, 2003;Pizam et al, 2004;Reisinger & Mavondo, 2005;Sönmez & Graefe, 1998b). Plog (1974; categorized tourists based on their personality and motivation into three scales.…”
Section: The Antecedents Of Risk Perceptionmentioning
confidence: 99%
“…There has been an increasing number of tourism studies on risk and safety since 1970s (Maser & Weiermair, 1998;Milman, Jones, & Bach, 1999;Pizam, 1999;Sirakaya, Sheppard, & McLellan, 1997;Sönmez, Apostolopoulos, & Tarlow, 1999;Sönmez & Graefe, 1998a, 1998bTsaur, Tzeng, & Wang, 1997;Wilks & Atherton, 1994). The term 'risk' was used extensively in tourism research after the 9/11 incident (Dickson & Dolnicar, 2004;Fuchs & Reichel, 2006;Korstanje, 2011;Law, 2006;Lepp & Gibson, 2003;Pizam et al, 2004;Quintal, Lee, & Soutar, 2010;Reisinger & Mavondo, 2005;Simpson & Siguaw, 2008;Williams & Baláž, 2013), followed by a couple of major tragedies including the SARS outbreak, the Bali bombings, and the Asian tsunami, which have shaken the tourism industry across the globe. The severity, frequency, and impact of these unprecedented tragedies have given rise to an increasing number of researches investigating the various aspects of risk in tourism.…”
Section: Introductionmentioning
confidence: 99%
“…According to tourism literature, tourists' perceptions of natural disasters and travel risks differ depending on their familiarity with a destination (Millman and Pizam 1995;Han 2005) and national culture (Bontempo et Seddighi et al 2001;Mavondo 2006a, 2006b). For example, significant differences in travel risk perception were found across various national cultures (Seddighi et al 2001;Fuchs and Reichel 2004;Pizam et al 2004;Movondo 2006a, 2006b). It was found that the risk perception of the Chinese significantly differs from that of Westerners (Bontempo et al 1997).…”
Section: Differences In the Perceptions Of Natural Disasters And Travmentioning
confidence: 99%
“…Similarly, Gibson and Jordan (1998) noted that females are more vulnerable to risk than males. Pizam et al (2004) found that men were more likely to seek spontaneous, adventure-filled experiences, and were less likely to change their travel plans when confronted with risks such as terrorism, health, and natural disasters. Qi, Gibson and Zhang (2009) in their study of U.S. travellers' perceptions of risk and travel to China and the 2008 Beijing Olympic Games found that women perceived much higher violence risk than men, whereas men expressed more concern about health risks.…”
Section: Perceived Risk and Tourismmentioning
confidence: 99%
“…Earlier studies show that an individual's perception of travel risk is affected by several behavioural characteristics such as purpose of visit (Rittichainuwat, Qu & Mongkhonvanit, 2002;George, 2010), length of stay Barker et al, 2003), past travel experience (Chen & Gursoy, 2001;Lepp & Gibson, 2003), and travel information search and sources (Pizam et al, 2004;Kozak, Crotts & Law, 2007). For instance, tourism-crime researchers have found that past experience can also affect perception of risk.…”
Section: Perceived Risk and Tourismmentioning
confidence: 99%